EFFECTIVENESS OF REFLECTIVE RIBBONS IN THE MANAGEMENT OF ROSE-RINGED PARAKEET (Psittacula krameri) IN GUAVA (Psidium guajava L.) ORCHARDS (Applied Biological Research, 2023)
Fruit loss due to birds is a long-standing and costly problem affecting  producers across the globe. The rose-ringed parakeet enjoys the status of  worst avian pest in the Indian subcontinent. This study provides the  information about the effectiveness of reflective ribbons in controlling the  damage of rose-ringed parakeet (Psittacula krameri) to guava (Psidium  guajava L.) fruit trees in central plain and sub-mountainous regions of  Punjab (India). Thdamage causedby parakeet to the control fields ranged from 12.13 to 16.76% while the fields installed with reflective ribbons had damage between 5.67 and 8.51%. Ripened fruits were more preferred with  top canopy most affected part of the trees. A remarkable reduction in bird  damage was noticed in presence of reflective ribbons. Therefore, it seems  plausible to use reflective ribbons as bird repellents to reduce bird  depredatory attacks, improve economic losses and augment the crop  quality and production.
Keywords: Avian pest; bird management canopy; guava; reflective ribbon; rose-ringed parakeet